The Almanac “Woman and Russia” and the Soviet Feminist Movement at the end of the 1970s - Milewska-Pindor, Nadina (International Studies. Interdisciplinary Political and Cultural Journal, 2013)
This article presents a short history of the origin and creation of the Almanac “Women and Russia,” which began as a samizdat underground publication devoted to the problem of women and childrearing in the USSR. The idea for creating such an Almanac originated in the mid 1970s in the Leningrad circle of ‘unofficial culture’, at the initiative of the artist Tatyana Mamonova, religious philosopher Tatyana Goricheva, and the women author Natasha Malachovska. The women writers featured in the first edition of the Almanac addressed not only questions about the social conditions prevailing in the USSR, but above all exposed the consequences for women living and functioning ina patriarchal social order, and ironically one where all the questions concerning ‘women’s rights’ were deemed to have been resolved in a progressive fashion much earlier. Not only is the substance of the Almanac important, but the circumstances surrounding its publication and the subsequent consequences related to its publishing also reveal the state of the ‘women’s movement’ in the USSR of that time. These include the reactions of the representatives of the dissident culture, the interventions of the security apparatus and the attendant repression of the women activists and its effect on their lives, and the support of feminist organizations from abroad. Each of the afore-mentioned reactions and consequences became an element of and shaped the everyday lives of the activists involved in the creation of the Almanac. The events related in this work confirm the opinion of those researchers who consider that the publication of the Almanac marked the beginning of the resurrection of the feminist movement in Russia.